2006
DOI: 10.1242/jcs.02998
|View full text |Cite
|
Sign up to set email alerts
|

The fission yeast Chs2 protein interacts with the type-II myosin Myo3p and is required for the integrity of the actomyosin ring

Abstract: In Schizosaccharomyces pombe cytokinesis requires the function of a contractile actomyosin ring. Fission yeast Chs2p is a transmembrane protein structurally similar to chitin synthases that lacks such enzymatic activity. Chs2p localisation and assembly into a ring that contracts during division requires the general system for polarised secretion, some components of the actomyosin ring, and an active septation initiation network. Chs2p interacts physically with the type-II myosin Myo3p revealing a physical link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 34 publications
(47 reference statements)
3
26
0
7
Order By: Relevance
“…Thus, it is not surprising that Cfh3p is 26 and 28% identical to ScChs4p and CaChs4p, respectively, and that these identity values only increase to 29 and 30%, respectively, when the comparison is restricted to the SEL1 domains. Our results show that Cfh3p plays a role in the regulation of glucan synthesis, in agreement with the idea that in S. pombe Chs-like proteins have maintained a general function not related to chitin synthesis, as reported for Chs2p and Cfr1p (42,46,47). In this case, the function would be to ensure the stabilization of enzymes involved in cell wall synthesis at the plasma membrane.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, it is not surprising that Cfh3p is 26 and 28% identical to ScChs4p and CaChs4p, respectively, and that these identity values only increase to 29 and 30%, respectively, when the comparison is restricted to the SEL1 domains. Our results show that Cfh3p plays a role in the regulation of glucan synthesis, in agreement with the idea that in S. pombe Chs-like proteins have maintained a general function not related to chitin synthesis, as reported for Chs2p and Cfr1p (42,46,47). In this case, the function would be to ensure the stabilization of enzymes involved in cell wall synthesis at the plasma membrane.…”
Section: Discussionsupporting
confidence: 91%
“…The following results are inconsistent with this conclusion. (i) In our previous work (46,47) and in this work we observed that Chs2p localized at internal vesicles in both the WT and the cfh3⌬ strain (supplemental Fig. S4), depending on the culture conditions.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Several membrane-associated proteins have been shown to ensure CAR integrity, including the F-BAR-containing proteins Cdc15 and Imp2 that bind to the CAR or the equatorial membrane (Celton-Morizur et al, 2004;Martín-García and Valdivieso, 2006;Roberts-Galbraith et al, 2009). We have found that Rga7 cooperates with Cdc15 and Imp2 in maintaining CAR stability, especially during contraction, as judged by the presence of uncompleted septa without CARs, when the function of Rga7 and Cdc15 or Imp2 is simultaneously affected.…”
Section: Discussionmentioning
confidence: 81%
“…The role of Chs2-Inn1-Cyk3 in mycelial fungi remains to be explored in the future, but the fission yeast proteins Chs2, Fic1 (the orthologue of Inn1: Fic15'Fifteen interacting C2-domain' as it interacts with the Cdc15 orthologue of ScHof1) and Cyk3 are known to be present at the cleavage site (Martín-García et al, 2003;Roberts-Galbraith et al, 2009;Pollard et al, 2012), though they only have a minor role in cytokinesis (Mishra et al, 2004;Martín-García and Valdivieso, 2006;Roberts-Galbraith et al, 2009;Pollard et al, 2012).…”
Section: Discussionmentioning
confidence: 99%